2009
DOI: 10.2147/ppa.s5691
|View full text |Cite
|
Sign up to set email alerts
|

Difficult to swallow: patient preferences for alternative valproate pharmaceutical formulations

Abstract: Objective:To determine the degree to which swallowing valproate (VP) tablets is an issue, the proportion of patients who would prefer an alternative formulation, and the predictors of preference.Methods:A quantitative telephone survey of eligible adults (n = 400, ≥18 years old) who currently take (n = 236) or previously took (n = 164) VP tablets within the past 6 months was conducted.Results:More than half of the patients indicated that VP tablets were ‘uncomfortable to swallow’ (68.5%, n = 274) and were ‘very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The aim of using different formulations is to improve acceptability to patients and accordingly increase compliance with treatment. Physicians should be aware of patient preferences when selecting a drug formulation [36]. For example, extended-release conventional tablets or medications with long halflives are an alternative because, while they do not address the problem with swallowing tablets, reducing the number of daily doses may help patients become more compliant.…”
Section: Facilitating Pill Swallowingmentioning
confidence: 99%
“…The aim of using different formulations is to improve acceptability to patients and accordingly increase compliance with treatment. Physicians should be aware of patient preferences when selecting a drug formulation [36]. For example, extended-release conventional tablets or medications with long halflives are an alternative because, while they do not address the problem with swallowing tablets, reducing the number of daily doses may help patients become more compliant.…”
Section: Facilitating Pill Swallowingmentioning
confidence: 99%
“…Recent studies have reported that more than a half of the interviewed patients with schizophrenia (n = 400) preferred orally disintegrating tablets (ODT) to other dosage forms, such as tablets, for swallowing or oral delivery. [5][6][7] In this sense, other forms of delivery, such as the use of chewable or dissolvable tablets, [8][9][10] or rapidly dissolving films, [11][12][13] could be advantageous; however, these forms must be preceded by the development of taste-masking formulations, owing to the unpleasant taste of APZ. Numerous approaches have been employed in the field of taste masking, most of which were have been based on the encapsulation of drugs inside polymeric materials, such as hydroxypropylmethylcellulose (HPMC), Eudragit EPO, and Abstract: Poor aqueous solubility and the unpleasant taste of aripiprazole (APZ) have been recurring problems, owing to its low bioavailability and low patient tolerance, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, the nanohybrids could be the base formulation for ODTs, which are the most favoured form of oral delivery by schizophrenia patients. [5][6][7] To accomplish taste masking, the release of the drug from the nanohybrids at the buccal cavity should be greatly suppressed. On the contrary, for enhanced drug bio-A C H T U N G T R E N N U N G availability, the release of the drug from the nanohybrids should be rapid and efficient, at least comparable to other commercially available medication, Abilify , through the gastrointestinal (GI) tract.…”
mentioning
confidence: 99%
“…In line with the previous results obtained by Motte et al (6), our data confirm the palatable property of VPA MR granule formulation and its positive influence on the convenience of use as the rate of the parents reporting troubles in the administration of VPA with MR granules was significantly lower than with solution. For its microsphere formulation, MR granules may be useful even in adults with difficulties in swallowing tablet formulation of VPA, as recently described (13).…”
Section: Discussionmentioning
confidence: 99%